Issue Salience and Candidate Position Taking in Parliamentary Parties. (May 2019) - Tromborg, Mathias
Research on parliamentary representation has traditionally assumed that political parties take clear and differentiated policy positions, but recent studies suggest that parties sometimes have an electoral incentive to present voters with a distribution of positions to select from at the ballot box. This article explores whether parliamentary parties pursue such a strategy through candidate position taking using unique elite and mass survey data from Denmark. The results illustrate that parties are highly unified on issues that are salient to their electoral brand, but that they develop a distribution of positions that is related to voter preferences at the district level on less salient issues. These findings have important implications for the way that representation works in parliamentary democracies.